Delta hepatitis in Rondônia: epidemiological analysis from 1999 to 2012 - Vieira, Gabriel de Deus; Coelho, Henrique Schroeder Affonso; Passos, Rodrigo Barbosa; Brum, Eloisa Barbosa; Pereira, Raquel Mascarenhas; Magalhães, Paula de Carvalho; Sousa, Camila Maciel de (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Hepatitis Delta virus (HDV) is considered an important cause of severe liver disease. Objective: This study aimed at an epidemiological analysis of cases diagnosed in Rondônia. Methods: A retrospective study from 1999 to 2012 was done through data provided by the State Agency of Health Surveillance of Rondônia (AGEVISA-RO). The variables analyzed were: year of diagnosis, gender, age, contact with patients known to have hepatitis B virus (HBV), ethnicity, vaccination, exposure to risk factors, mechanism of infection and clinical manifestation. Results: 149 cases have been reported, with an average incidence of 0.7 cases per 100,000 inhabitants/year; 62.4% of these were males and 5.3%, females. The most common age group was between 20 and 39 years. About hepatitis B vaccination, the majority took no vaccine dose. The most common route of transmission was sexual (71.8%), and most patients were in the chronic phase of the disease (95.9%). Conclusion: The population affected by the virus is mainly composed of men in the sexually active age group, with sexual intercourse as the main mode of transmission. Low adherence to vaccination by the population affected was observed; thereby, measures of education and public awareness are needed.